The Effect of Observing Entrepreneurial Role Models on Critical Thinking Skills in Entrepreneurship Learning - Janata, Ade Dwi Putra; Sudira, Putu; Sutarto, Sutarto; Mutohhari, Farid (Jurnal Pendidikan Progresif, 2022)
The effect of observing entrepreneurial role models on critical thinking skills in entrepreneurship learning. Objectives: This research analyzes a PBL model by observing an entrepreneurial role model's effect on the critical thinking skills in entrepreneurship learning at Vocational High School. Methods: This study uses quasi-experimental research with a quantitative approach. The total population in this study was 463 students, and a sample of 60 students was obtained using a simple random sampling technique which was divided into two groups. This study uses an instrument essay questions tests in the form of pre-test and post-test. t-test analysis was conducted to test the hypothesis with a significance level of 5%. Findings: The results of the paired sample t-test obtained sig (2 tailed) 0.000 < 0.05. Thus rejecting H0 and accepting Ha. Conclusion: Observing an entrepreneurial role model significantly affects the critical thinking skills in entrepreneurship learning at Vocational High School. Keywords: entrepreneurial role model, critical thinking skills, entrepreneurship learning.DOI: http://dx.doi.org/10.23960/jpp.v12.i3.202220